Potential dopant in photocatalysis process for wastewater treatment-a review - Razali, N. A.; Othman, S. A . (2021)
Nowadays, too much pollution has happened around us, and one of them is water pollution, which each day has become more severe and worse. One of the sources of water pollution comes from the industry that has used dyes either excessively or not. In case of that, the wastewater needs to be treated before released to the river or environment. In this paper, a review of the wastewater treatment using dopants such as nitrogen and magnesium, will be discussed.